Factors Predicting Spiritual Well-Being among Dependent Older People - Trapsinsaree, Doungmon; Pothiban, Linchong; Chintanawat, Rojanee; Wonghongkul, Tipaporn (Trends in Sciences, 2022)
Spiritual well-being is a deep feeling within the mind that represents peacefulness and the inner strength of individuals, resulting from an understanding of the nature of life and acceptance of changes occurring to themselves. Spiritual well-being is; therefore, very important to dependent older people. The objectives of this study were to identify the levels of spiritual well-being of dependent older people, to examine the relationships between religious belief, religious practice, self-esteem, social support, depression, and spiritual well-being, and to examine the ability of those factors to predict spiritual well-being among dependent older people. The study sample were 395 of people aged 60 years and above who are dependent and live in three provinces in southern Thailand. Data were collected using questionnaires, including the Spiritual Well-Being Scale for Dependent Older People, Thai version of the Rosenberg Self-Esteem Scale, Thai version of the Multidimensional Scale of Perceived Social Support, Thai Geriatric Depression Scale, the Religious Practices Questionnaire, and the Buddhist Belief Questionnaire. Data were analyzed using descriptive statistics, Spearman’s rank correlation coefficient, and multiple regression analysis. The study results were as follows: 1) The spiritual well-being among dependent older people was at a moderate level (x̅ = 46.97, SD = 7.22). 2) Religious belief, religious practice, self-esteem, and social support significantly related positively to spiritual well-being (p < 0.01), while depression significantly related negatively to spiritual well-being (p < 0.01). 3) Religious belief, self-esteem, and social support together could explain 46.00 % of the variance in spiritual well-being. The results of this study can be used by nurses and health care providers to determine interventions for enhancing spiritual well-being in this particular group of older people. HIGHLIGHTS Spiritual well-being is one of the important dimensions of holistic care. Spiritual well-being has a positive effect on physical, mental and social health The conceptual framework is guided by the Buddhism Principles Religious belief, self-esteem, and social support together could explain 46.00 % of the variance in spiritual well-being